Prioritizing conservation for the reduction of Gulf hypoxia using an environmental performance index. (July 2016) - Barnhart, Brad; Bostian, Moriah; Whittaker, Gerald; Grosskopf, Shawna; Färe, Rolf
Abstract: The annual growth of hypoxia in the Gulf of Mexico is largely attributed to agricultural nutrient loadings that originate from the Mississippi/Atchafalaya River Basin (MARB). To effectively target conservation efforts throughout the entire MARB in order to reduce Gulf hypoxia, strategies to rank areas according to their impact on both agricultural production and ecosystem services are extremely important. In this paper, we utilize an Environmental Performance Index (EPI) to rank regions within the MARB according to their environmental performance, that is, their ability to produce agricultural outputs while minimizing nutrient loadings to the Gulf of Mexico. We compare our index rankings to previously used rankings of delivered yields alone and find the spatial distribution of rankings changes considerably when accounting for agricultural productivity. For example, the Corn Belt regions of central Iowa and northern Illinois no longer make up the lowest performing regions of the MARB after accounting for their high levels of agricultural production. Instead, regions along the Missouri river including central Missouri, western Iowa, and southeastern South Dakota as well as areas near the Ohio river including southern Illinois, western Kentucky, and southern Ohio now count among the lowest performing regions using the EPI ranking scheme. We suggest that incorporation of economic production value into large-scale prioritization of agricultural conservation within the MARB is essential to effectively reduce Gulf hypoxia while maintaining food security from efficient farm production.